Evaluation of the clinical performance of noninvasive prenatal testing at a Japanese laboratory. Issue 10 (5th August 2021) - Sasaki, Yuna; Yamada, Takahiro; Tanaka, Shiro; Sekizawa, Akihiko; Hirose, Tatsuko; Suzumori, Nobuhiro; Kaji, Takashi; Kawaguchi, Satoshi; Hasuo, Yasuyuki; Nishizawa, Haruki; Matsubara, Keiichi; Hamanoue, Haruka; et al.
Abstract: Aim: We aimed to evaluate the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of noninvasive prenatal testing (NIPT) in high‐risk pregnant women. Methods: Pregnant women who underwent GeneTech NIPT, the most commonly used NIPT in Japan, between January 2015 and March 2019, at Japan NIPT Consortium medical sites were recruited for this study. The exclusion criteria were as follows: pregnant women with missing survey items, multiple pregnancy/vanishing twins, chromosomal abnormalities in the fetus other than the NIPT target disease, and nonreportable NIPT results. Sensitivity and specificity were calculated from the obtained data, and maternal age‐specific PPV and NPV were estimated. Results: Of the 45 504 cases, 44 263 cases fulfilling the study criteria were included. The mean maternal age and gestational weeks at the time of procedure were 38.5 years and 13.1 weeks, respectively. Sensitivities were 99.78% (95% confidence interval [95% CI]: 98.78–99.96), 99.12% (95% CI: 96.83–99.76), and 100% (95% CI: 88.30–100) for trisomies 21, 18, and 13, respectively. Specificities were more than 99.9% for trisomies 21, 18, and 13, respectively. Maternal age‐specific PPVs were more than 93%, 77%, and 43% at the age of 35 years for trisomies 21, 18, and 13, respectively. Conclusion: The GeneTech NIPT data showed high sensitivity and specificity in the detection of fetal trisomies 21, 18, and 13 in high‐risk pregnant women, and maternal age‐specific PPVs were obtained. These results could provide more accurate and improved information regarding NIPT for genetic counseling in Japan.